2020
DOI: 10.1002/hyp.13779
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of litter covering and incorporation on infiltration and soil erosion under simulated rainfall

Abstract: Plant litter can either cover on soil surface or be incorporated into top‐soil layer in natural ecosystems. Their effects on infiltration and soil erosion are likely quite different. This study was performed to compare the effects of litter covering on soil surface and being incorporated into top‐soil layer on infiltration and soil erosion under simulated rainfall. Four litter types (needle‐leaf, broad‐leaf, brush, and herb) were collected from fields and applied to cover on soil surface or to be incorporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…As determined in this study, the water-holding capacity of the semi-decomposed and non-decomposed litter layers was significantly different due to the changes in litter coverage and morphological characteristics 25 29 . The maximum water-holding capacity of the semi-decomposed litter layer is greater compared to the litter non-decomposed layer, which is consistent with previous results 40 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As determined in this study, the water-holding capacity of the semi-decomposed and non-decomposed litter layers was significantly different due to the changes in litter coverage and morphological characteristics 25 29 . The maximum water-holding capacity of the semi-decomposed litter layer is greater compared to the litter non-decomposed layer, which is consistent with previous results 40 .…”
Section: Discussionmentioning
confidence: 60%
“…By studying the effects of different vegetation litters on the characteristics of overland flow, Sun et al 28 found that litter coverage could significantly reduce the Reynolds number and flow power by 8–29% and 56–80%, respectively. Wang et al 29 studied the effects of four types of litter coverage and incorporation on soil erosion and found that the amount of erosion under litter-incorporated treatment was 5.4 times as large as that of litter-covered treatment. As mentioned above, litter affect hydrological and erosion processes greatly.…”
Section: Introductionmentioning
confidence: 99%
“…Surface erosion or the release of the soil surface due to water flow can The litter layer is very influential in the magnitude of the kinetic energy of rain on the soil surface. Without a surface cover, raindrops can hit the soil surface and cause the surface layer to be released [Wang et al, 2020]. Mechanically, this process takes place continuously and causes an increase in the slope of the slope.…”
Section: Discussionmentioning
confidence: 99%
“…Litter types, coverage, quality, and other variables have an impact on slope soil erosion. Wang [18] compared the slopes covered by locust, pine, caragana and switchgrass with bare slopes and confirmed that the soil loss rate was reduced by 91%, 35%, 74% and 80%, respectively. Li [19] contrasted two typical litters on the loess plateau and found that the flow velocity on the slope decreased with the increase of litter cover as a power function.…”
Section: Introductionmentioning
confidence: 87%